Teaching Academic Vocabulary to Sixth-Grade Students With Disabilities. (November 2019) - O'Connor, Rollanda E.; Beach, Kristen D.; Sanchez, Victoria M.; Kim, Joyce J.; Knight-Teague, Kerri; Orozco, Guadalupe; Jones, Brian T.
Adolescents with disabilities have great difficulty with academic content in middle school, and their teachers have difficulty teaching them to understand and use academic language. We taught teachers of sixth-grade students with learning disabilities, more than half of whom were also English language learners (ELLs), to implement about 15 min of daily interactive vocabulary instruction in their intact special education English/language arts classes. Three schools were assigned randomly to treatment (two schools) or control conditions (one school, 52 students total). We developed instructional routines to introduce four new words per week in three 4-week units to test for replicability. ANCOVAs (with each cycle's pretest and intelligence quotient as covariates) were conducted on taught vocabulary, all of which favored the treatment condition with effect sizes ranging .6 to .7 per cycle. Near-transfer effects to vocabulary usage were weaker, with significant effects in the last two cycles. Effects were similar for students with disabilities who were ELLs and native English speakers. Treated students maintained their knowledge of words 4 to 24 weeks following the close of treatment.